The Attractiveness of Food Images and Attractiveness of Behind The-Scenes in Consumer Engagement in Social Media - Dafa H.D, Krisna; Surayya Ulfa, Nurist; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
This study aims to analyze the influence of the attractiveness of food images (X1) and the attractiveness of behind-the-scenes (BTS) food video reels (X2) on consumer engagement in social media. With the rapid development of social media platforms, especially in the food and beverage industry, visual factors have become crucial elements in attracting consumer attention. This research proposal identified that visual content plays a significant role in shaping consumer engagement on social media, with the two main variables being the attractiveness of food images and BTS food video reels. The approach used in this study is multiple regression analysis to measure the extent to which these two independent variables affect consumer engagement on social media. Data were collected through a questionnaire survey distributed to consumers in the food and beverage industry. The results indicate that both independent variables, the attractiveness of food images (X1) and the attractiveness of BTS food video reels (X2), have a significant impact on consumer engagement on social media. Specifically, the attractiveness of food images (X1). This indicates that attractive visual content significantly enhances consumer engagement on social media. The conclusion of this study emphasizes the importance of attractive visual content in social media marketing strategies. Social media account managers in the food and beverage industry are advised to improve the quality of the images and videos they upload, particularly BTS videos, to maximize consumer engagement. This research provides significant contributions to understanding the dynamics of consumer engagement on social media and offers practical guidelines for industry practitioners